2020
DOI: 10.22610/jebs.v12i4(j).3063
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Local Governments Financial Performance

Abstract: This study aims to test and prove the relationship of local government financial performance with fiscal balance transfer, local own-source revenue, local government size, and capital expenditure. The study uses samples from District/City Local Governments in Sulawesi Island for the years 2016-2018. The samples were collected using the census sampling method, for a total of 243 samples in District/City Local Governments in Sulawesi Island. In this analysis, the hypothesis testing is performed using SPSS by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
2
2
0
Order By: Relevance
“…The study findings are consistent with the agency theory, which argues that LG trusts residents to manage regional wealth for the benefit of the entire community. The findings of this study are consistent with a number of earlier studies, including those by Aswar ( 2019), Amalina and Sumardjo (2020), Samadara et al ( 2021), Oktaviani et al (2020), and Simanullang (2013), which found a strong correlation between regional wealth as measured by PAD and LG financial performance. Furthermore, it was discovered that the intergovernmental revenue had a t-value > ttable, 4.768 > 1.648, and a significance level of 0.000 0.05.…”
Section: Nosupporting
confidence: 92%
See 3 more Smart Citations
“…The study findings are consistent with the agency theory, which argues that LG trusts residents to manage regional wealth for the benefit of the entire community. The findings of this study are consistent with a number of earlier studies, including those by Aswar ( 2019), Amalina and Sumardjo (2020), Samadara et al ( 2021), Oktaviani et al (2020), and Simanullang (2013), which found a strong correlation between regional wealth as measured by PAD and LG financial performance. Furthermore, it was discovered that the intergovernmental revenue had a t-value > ttable, 4.768 > 1.648, and a significance level of 0.000 0.05.…”
Section: Nosupporting
confidence: 92%
“…The study findings are consistent with the stakeholder theory, which claims that when a stakeholder-in this case, the community represented by the DPRD-grants the LG manager full authority to oversee and administer the government, it functions at its best. The findings of this analysis are consistent with a number of earlier studies, particularly those by Oktaviani et al (2020) and Mulyani and Wibowo (2017), which found that capital expenditure had a considerable impact on LG's financial performance. The moderating variable, political monitoring, which modifies the association between regional wealth and LG financial performance, has a significant level of 0.001 to 0.05 and a t-value greater than the t-table, or 3.403 > 1.648.…”
Section: Nosupporting
confidence: 90%
See 2 more Smart Citations
“…A high independence ratio, good efficiency in the use of resources, and appropriate fiscal decentralisation can result in an increase in capital expenditure, which has a positive impact on economic growth. Studies conducted [15,16] have explored various factors that influence local government financial performance, including the impact of capital expenditure. Research [15,16] shows a positive relationship between financial performance and capital expenditure.…”
Section: Relationship Between Financial Performance and Capital Expen...mentioning
confidence: 99%